2020
DOI: 10.1101/2020.09.11.283168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishing a Living Biobank of Patient-Derived Organoids of Intraductal Papillary Mucinous Neoplasms of the Pancreas

Abstract: Pancreatic cancer (PaCa) is the third leading cause of cancer-related deaths in the United States. There is an unmet need to develop strategies to detect PaCa at an early, operable stage and prevent its progression. Intraductal papillary mucinous neoplasms (IPMNs) are cystic PaCa precursors that comprise nearly 50% of pancreatic cysts detected incidentally via cross-sectional imaging. Since IPMNs can progress from low- and moderate-grade dysplasia to high-grade dysplasia and invasion, the study of these lesion… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The tumor tissues were first digested with a proteolytic enzyme for cell retrieval. The recovered cancer cells were then seeded in Matrigel ® and stored as PDOs in a living biobank (119). The gene analysis data of key markers KRAS, PTEN, PIK3CA, GNAS, RNF43, and BRAF showed a similar expression between PDO and the patient's tumor tissue biopsy, which confirmed the preservation of patient samples' genome in living biobanks.…”
Section: Overcoming the Limited Source Of Patient-derived Organoidsmentioning
confidence: 59%
See 1 more Smart Citation
“…The tumor tissues were first digested with a proteolytic enzyme for cell retrieval. The recovered cancer cells were then seeded in Matrigel ® and stored as PDOs in a living biobank (119). The gene analysis data of key markers KRAS, PTEN, PIK3CA, GNAS, RNF43, and BRAF showed a similar expression between PDO and the patient's tumor tissue biopsy, which confirmed the preservation of patient samples' genome in living biobanks.…”
Section: Overcoming the Limited Source Of Patient-derived Organoidsmentioning
confidence: 59%
“…Fortunately, PDOs can be replicated and cryopreserved in specialized facilities, known as living biobanks, without losing cell-type specificity (87,118). For example, intraductal papillary mucinous neoplasms were collected from patients with pancreatic cancer (119). The tumor tissues were first digested with a proteolytic enzyme for cell retrieval.…”
Section: Overcoming the Limited Source Of Patient-derived Organoidsmentioning
confidence: 99%
“…We will also be performing genotyping for ancestry informative markers using DNA from blood collected via this study to validate self-reported ancestry. Finally, based on the promise of pre-clinical models in translational efforts [79][80][81][82][83] , we also plan to leverage the pancreatic tissue collected and preserved through this effort for applications such as generation of patient-derived organoids 105 . Thus, the biospecimens collected by the FPC will become an enduring resource for the biomedical and disparities research community.…”
Section: Discussionmentioning
confidence: 99%